Islam Transformation, Diaspora, and The Locality Response of Java’s Religion: An Indonesian Fiction Studies - Akhmad Taufiq (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2022)
Abstract: The process of Islam transformation as a great religion however is massively received in Nusantara, recognized or not can bring its own problems for the local religion that has been long existed. In such cases, this study aims to describe the locality response of local religion in Java over the incessant process of the great religion transformation and diaspora. By the literature sociological approach, this study sought to describe the locality response as reflected in fiction Indonesia, namely Serat Darmogandul by K.R.T.Tandhanagara and novel Putri Cina by Sindhunata. By the analysis of genetic structuralism, the results of this study stated that that the process of transformation, the diaspora, and the response of the locality in the context of local religion in Java presupposelinearity pattern of cultural process for the cultural transition that occurred in Java. After the collapse of Majapahit who embrace Buddhism (the religion of Shiva-Buda religious/Java) who then turn to the rule of Islam in the Sultan of Demak, showing intertwined process between the dimension of power and religion. The intertwined process shows that the power dimensions and religiondimensions that seem inseparable; on the contrary, interwoven in their entirety. Therefore, the implications of this study are expected to contribute to the process of positioning the local religion more adequately in the context of the transformation and the religion diaspora that exists and keep going until today.